War poems - Pope, Jessie (PORTABLE POETRY, 2017)
"Jessie Pope was born on 18th March 1868, in Leicester and was educated at North London Collegiate School. She was a regular contributor to many publications including Punch, The Daily Mail and The Daily Express, also writing for Vanity Fair, Pall Mall Magazine and the Windsor. Pope stands almost alone as an English female poet who was decidedly and patriotically vocal about the War. This was in marked contrast to her male colleagues, many of whom were soldier-poets, who, under slaughter in the in the trenches, were almost all against it. Her war poetry, mainly published in the Daily Mail, encouraged a public duty for enlistment and, shockingly, would hand a white feather to youths who would not join the colours. From todays' perspective the poetry is jingoistic, with its simple rhythms and extensive use of rhetorical questions to persuade and pressure young men to join the war. Wilfred Owen in particular called her efforts into question with his poem Dulce et Decorum Est which was originally dedicated 'To Jessie Pope etc.' However, to balance this her war poetry between 1914-18 can be compartmentalised. Some, such as 'War Girls' do have a flavour of women's rights attached to them and when her other works are included it can be seen that her reputation before the war was of a humourist and writer of light verse. She was even described, pre-war, as the 'foremost woman humourist' of her day. Her other verse has also been used to show sympathetic portrayals of the poor and powerless. Her portrayal of the Suffragettes in a pair of counterpointed 1909 poems makes a case both for and against their actions. After the war, Pope continued to write; a novel, poems and children's books. At age 61, she married a widower bank manager in 1929, and moved from London to Fritton, near Great Yarmouth. Jessie Pope died on 14th December 1941, in Devon."--EBSCO.